Genetically Modified Fish in Future Aquaculture: Technical, Environmental and Management Considerations - Aleström, Peter (International Service for National Agricultural Research, 2001)
Statistics on global fish and shellfish production show that fish farming represents about 15% of the global fish yields and is expected to exceed 20% by the year 2000. Capture fisheries have already reached their maximum sustainable yield, and this why any increase in seafood production can only be achieved through aquaculture. Increased productivity in aquaculture will be achieved through genetic improvement of species by selection breeding and, potentially, gene transfer technology.